Proximity of food retailers to schools and rates of overweight ninth grade students: an ecological study in California - Fulfrost Brian; Fitzpatrick Margaret; Howard Philip H (BMC, 2011)
Abstract Background The prevalence of obesity and overweight in youth has increased dramatically since the 1980s, and some researchers hypothesize that increased consumption of low-nutrient, energy-dense foods is a key contributor. The potential importance of food retailers near schools has received increasing attention, but public health research and policy has focused primarily on fast food restaurants. Less is known about the relationship between overweight/obesity and other types of retailers. This study aims to investigate the potential associations between nearby 1) fast food restaurants, 2) convenience stores, and 3) supermarkets, and rates of overweight students in California schools. Methods We examined the rate of overweight ninth grade students in public schools in 2007 using linear regression. The percentage of overweight students per school was determined by a state required physical fitness test, with three different options for measuring individual body composition. Our key independent variables were the presence of three different types of retailers within 800 m network buffers of the schools. Additional independent variables included school ethnic, gender and socioeconomic composition, as well as urban/non-urban location. We obtained the data from the California Department of Education and ESRI, Inc. Results The presence of a convenience store within a 10-minute walking distance of a school was associated with a higher rate of overweight students than schools without nearby convenience stores, after controlling for all school-level variables in the regression (1.2%, 95% confidence interval 0.03, 2.36). Nearby fast food restaurants and supermarkets, however, were not associated with school rates of overweight students. Conclusions Public health researchers and policy-makers interested in the food environments outside schools should expand their recent focus on nearby fast food restaurants to include convenience stores, which may also be important sources of low-nutrient, energy-dense foods for students.